A Comparative Study on the Growth of Oyster Mushroom in Different Substrates - Margaret, I. Viji; Praba, l. Jeya; Sathiya, G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Mushrooms are cultivated worldwide for their taste, nutritional attributes, and potential application industries. The edible oyster mushrooms Pleurotus florida and Hypsizygus ulmarius were selected for the present study. The different organic wastes such as paddy straw, coconut dry leaves, and palm dry leaves were used as the substrates for mushroom cultivation. Among the three substrates, paddy straw is a good substrate and provides a good yield of oyster mushrooms. Because paddy straw contains higher quantities of minerals and irons than other substrates which are needed for the growth of mushrooms. Pleurotus florida showed a total weight yield of 1.250 gm and Hypsizygius ulmarius was 1.300 gm Mycelium growth was very slow in the palm and coconut leaves. Meanwhile, mycelium was quickly grown in paddy straw. Cultivation of Pleurotus florida, Hypsizygius ulmarius oyster mushrooms on paddy straw was proven as the best substrate and follow the concept of conversion of agricultural waste into value-added products.